The Dynamics of Municipal Fiscal Adjustment - Thiess Buettner; David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2002)
The dynamic fiscal policy adjustment of local jurisdictions is investigated empirically using a panel of more than 1000 U.S. municipalities over a quarter of a century. Distinguishing own revenues, grants, expenditures, and debt service, the analysis is carried out using a vector error correction model which takes account of the intertemporal budget constraint. The results indicate that a large part of the fiscal adjustment to changes in any budgetary component takes place by an offsetting change in future expenditures. In addition, the results point to an important role of grants in maintaining budget balance as lower revenues and higher expenditures including debt service are followed by significant increases in grants. Decompositions of the sample according to average city population and initial debt burden reveal significant differences across subsamples. In particular, the role of grants in maintaining budget balance is much more pronounced with large cities whereas small cities tend to rely more on own revenues. Grants also play a more important role in the adjustment of cities with an initially high debt burden.
Keywords: H72; H74; H77; 330